Advanced yield trial on ash gourd under telangana climatic conditions - K.SUSHMA, K. DHANUMJAYA RAO and (The Journal of Research, PJTSAU, 2017)
An experiment Advanced Yield Trial on Ash gourd was conducted for three consecutive years from 2009 to 2012 at Vegetable Research Station, Hyderabad for evaluate the germplasm lines from different areas and to evaluate them for their earliness. For the evaluation of different genotypes of ash gourd (9) for their vegetative and fruit characters along with check shakthi. It was observed that, Bh-27 was recorded maximum average vine length (10.3 m) followed by Bh-24 (9.6 m) over shakti (7.9 m). Highest no. of branches/vine was recorded in Bh-1 (6.9) over shakthi (6.7). The no. of nodes at which first male flower was recorded in Bh-10 (14.5) followed by Bh-1 (14.9) over shakthi (20.9) and the first female flower was recorded in Bh-5 (14.0) followed by Bh-24 (14.3) over shakthi (20.5) which indicates earliness. The average no. of fruits/vine was recorded maximum in Bh-10 (4.4) followed by Bh-3 (4.3) over control (3.2). Highest average fruit weight was recorded in Bh-24 (15.9 kg) followed by Bh-27 (14.8 kg) over check (9.8 kg). Maximum fruit yield/vine was recorded in Bh-27 (54.2 kg) followed by Bh-24 (53.3 kg) over shakthi (48.0 kg).